Հայ մատենագիտության արդի վիճակը - Գրիգորյան, Մայա (Հայաստանի ազգային գրադարան)
National Library of Armenia is the main center in Republic of Armenia in charge for creation of national bibliographies. In the article the history of bibliographic work and structure of bibliographic lists is provided.
Keywords: Գրադարանագիտություն; Մատենագիտություն